2004
DOI: 10.1159/000080464
|View full text |Cite
|
Sign up to set email alerts
|

Is AV Fistula Patency Associated with Angiotensin-Converting Enzyme (ACE) Polymorphism and ACE Inhibitor Intake?

Abstract: Background/Aims: Hemodialysis treatment requires a well-functioning vascular access. Access patency is limited by the development of venous intimal hyperplasia, which predisposes to fistula stenosis and subsequent thrombosis. In animal models, the renin-angiotensin system has a major role in the development of intimal hyperplasia. We investigated the association of the insertion/deletion polymorphism of the angiotensin-converting enzyme (ACE) and arteriovenous fistula patency in hemodialysis patients. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 35 publications
2
31
2
Order By: Relevance
“…In this study, renin-angiotensin system inhibition was observed as having limited ability to prevent AV stenosis. 32 The limitations of this study were insufficient II allele and lack of information in some patients about the usage of ACEI and AT-1 antagonist. We also noticed that usage of ACEI and ARB did not prevent early-stage AVF thrombosis.…”
Section: Discussionmentioning
confidence: 89%
“…In this study, renin-angiotensin system inhibition was observed as having limited ability to prevent AV stenosis. 32 The limitations of this study were insufficient II allele and lack of information in some patients about the usage of ACEI and AT-1 antagonist. We also noticed that usage of ACEI and ARB did not prevent early-stage AVF thrombosis.…”
Section: Discussionmentioning
confidence: 89%
“…This interindividual variation may relate to differences in the genetic background that may influence susceptibility to vascular inflammation and neointima formation after endothelial and smooth muscle injury. 6,7 Consistent with this notion, AVF survival was reported to be associated with specific genetic polymorphisms of transforming growth factor (TGF)-␤1 8 and methylene tetrahydrofolate reductase. 9 In addition, we recently identified a length polymorphism in the heme oxygenase-1 (HO-1) gene that is associated with patency of AVFs.…”
mentioning
confidence: 78%
“…Causative factors include a small artery (Ͻ1.5 to 2 mm) and a small vein (Ͻ2.0 to 2.5 mm), surgical manipulation and less-than-ideal technique, previous venipunctures, the development of accessory veins that direct blood away from the primary venous drainage channel, hemodynamic stressors (see below), and a possible genetic predisposition to vasoconstriction and neointimal hyperplasia after endothelial and smooth muscle injury (18,19). It still is unclear whether vascular constriction, neointimal hyperplasia, or a combination of the two factors is responsible for the early maturation failure of native fistulae.…”
Section: Pathogenesis Of Avf and Ptfe Graft Failurementioning
confidence: 99%